2020
DOI: 10.1093/brain/awaa178
|View full text |Cite
|
Sign up to set email alerts
|

Early-infantile onset epilepsy and developmental delay caused by bi-allelic GAD1 variants

Abstract: Gamma-aminobutyric acid (GABA) and glutamate are the most abundant amino acid neurotransmitters in the brain. GABA, an inhibitory neurotransmitter, is synthesized by glutamic acid decarboxylase (GAD). Its predominant isoform GAD67, contributes up to ∼90% of base-level GABA in the CNS, and is encoded by the GAD1 gene. Disruption of GAD1 results in an imbalance of inhibitory and excitatory neurotransmitters, and as Gad1−/− mice die neonatally of severe cleft palate, it has not been possible to determine any pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 34 publications
0
30
0
4
Order By: Relevance
“…Impairment of GABA synthesis or GABA neuron activity is thought to lead to neurodevelopmental disorders, epilepsy, and psychiatric disorders. For instance, GABA synthesis failure by bi-allelic loss-of-function mutations in the GAD1 gene causes early infantile epilepsy, severe cleft palate, and neonatal death ( 19 , 20 ). In addition, reduced GABAergic neuronal activity, abnormal brain activity, or GABA markers in postmortem studies have been observed in epilepsy ( 21 ), autism ( 22 , 23 ), schizophrenia ( 24 ), Alzheimer's disease ( 25 ), Down's Syndrome ( 26 ), and bipolar disorder ( 27 ).…”
Section: Gabaergic Genes and Gaba-related Genetic Disordersmentioning
confidence: 99%
“…Impairment of GABA synthesis or GABA neuron activity is thought to lead to neurodevelopmental disorders, epilepsy, and psychiatric disorders. For instance, GABA synthesis failure by bi-allelic loss-of-function mutations in the GAD1 gene causes early infantile epilepsy, severe cleft palate, and neonatal death ( 19 , 20 ). In addition, reduced GABAergic neuronal activity, abnormal brain activity, or GABA markers in postmortem studies have been observed in epilepsy ( 21 ), autism ( 22 , 23 ), schizophrenia ( 24 ), Alzheimer's disease ( 25 ), Down's Syndrome ( 26 ), and bipolar disorder ( 27 ).…”
Section: Gabaergic Genes and Gaba-related Genetic Disordersmentioning
confidence: 99%
“…Of note, an association between de novo loss-of-function variants in KIF17 and neurodevelopmental phenotypes, including abnormal behavior and schizophrenia, was previously proposed [ 18 ]. Different genes encoding kinesins and motor proteins have been previously implicated in brain development, and defining the full spectrum of disease-causing molecular pathways will help to diagnose, monitor, and accelerate treatment development in genetic neurodevelopmental conditions with associated cytoskeleton alterations or modulating ionotropic glutamate receptor subunits [ 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite being in the era of next-generation sequencing (NGS), the etiology and disease mechanisms underlying regressive neurodevelopmental impairment remain undetermined in a certain proportion of cases [ 4 , 5 ]. Defining the full spectrum of disease-causing molecular pathways underlying neurodevelopmental disorders will help to diagnose and monitor developmental trajectories in children affected with these conditions [ 6 , 7 , 8 , 9 , 10 , 11 ]…”
Section: Introductionmentioning
confidence: 99%